Spatial and temporal changes in electricity demand regulatory during pandemic periods: The case of COVID-19 in Doha, Qatar. (May 2022) - Al-Awadhi, Talal; Abulibdeh, Ammar; Al-Masri, Ahmed N.; Bin Touq, Ahmad; Al-Barawni, Mohammed; El Kenawy, Ahmed M.
Abstract: The propagation of the pandemic times, especially during COVID-19, has caused millions of morbidity and mortality cases across the world, forcing people to change their lifestyles and governments to take different measures to slow down the spread of the disease. Consequently, electricity demand and consumption patterns across other socioeconomic sectors were affected by the pandemic. This study aims to investigate the impact of the COVID-19 pandemic on spatiotemporal electricity demand and consumption across six socioeconomic sectors in Doha City, Qatar. The electricity demand and consumption were assessed for three time periods in the pandemic year (pre-lockdown, lockdown, and post-lockdown) compared to electricity consumption prior to the pandemic year (2017–2019). The empirical analysis was performed on a geographically visualized map to determine the areas with high and low electricity consumption. The pattern has been compared before and during the pandemic with previous years. The results show that electricity consumption has increased in the residential and governmental sectors and declined in the industrial and commercial sectors during the lockdown period compared to the post-lockdown period, particularly in the summer season. Mapping the hot/cold spots areas and the temporal analysis of the changing patterns of electricity demand and consumption could provide useful insight to decision-makers for targeted interventions. Highlights: This study investigate the impact of the COVID-19 pandemic on spatiotemporal electricity demand. The consumption pattern has been compared before and during the pandemic. Mapping the hot/cold spots areas and performing temporal analysis. Electricity consumption has increased in the residential and governmental sectors. Electricity consumption declined in the industrial and commercial sectors during the lockdown period.